2005
DOI: 10.1021/ct050133g
|View full text |Cite
|
Sign up to set email alerts
|

Modeling β-Scission Reactions of Peptide Backbone Alkoxy Radicals:  Backbone C−C Bond Fission

Abstract: To model the C-C β-scission reactions of backbone peptide alkoxy radicals, enthalpies and barriers for the fragmentation of four substituted alkoxy radicals have been calculated with a variety of ab initio molecular orbital theory and density functional theory procedures. The high-level methods examined include CBS-QB3, variants of the G3 family, and W1. Simpler methods include HF, MP2, QCISD, B3-LYP, BMK, and MPW1K with a range of basis sets. We find that good accuracy can be achieved with the G3(MP2)//B3-LYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 42 publications
(53 reference statements)
2
16
1
Order By: Relevance
“…Specifically, the U-CBS-QB3 without spin correction [26][27][28][29] correlates best with the W1U without spin correction, the CBS-QB3 with spin correction correlates best with the W1Usc with spin correction, and the ROCBS-QB3 correlates best with the standard W1͑RO͒ calculations. Specifically, the U-CBS-QB3 without spin correction [26][27][28][29] correlates best with the W1U without spin correction, the CBS-QB3 with spin correction correlates best with the W1Usc with spin correction, and the ROCBS-QB3 correlates best with the standard W1͑RO͒ calculations.…”
Section: Correlation Between Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, the U-CBS-QB3 without spin correction [26][27][28][29] correlates best with the W1U without spin correction, the CBS-QB3 with spin correction correlates best with the W1Usc with spin correction, and the ROCBS-QB3 correlates best with the standard W1͑RO͒ calculations. Specifically, the U-CBS-QB3 without spin correction [26][27][28][29] correlates best with the W1U without spin correction, the CBS-QB3 with spin correction correlates best with the W1Usc with spin correction, and the ROCBS-QB3 correlates best with the standard W1͑RO͒ calculations.…”
Section: Correlation Between Methodsmentioning
confidence: 94%
“…In a highly spin-contaminated species such as the cyano radical, this spin correction, −0.009 54E h ϫ⌬͗S 2 ͘, reduces the error in the unrestricted coupled-cluster 22 singles and doubles with perturbative triples [23][24][25] ͓UCCSD͑T͔͒ energy to a value comparable to that for species with little or no spin contamination ͑Fig. [26][27][28][29] The validity of this approach is reexamined in this study. However, in a number of recent studies of species with less severe spin contamination, [26][27][28][29] it has been found that inclusion of the spin correction term can sometimes lead to poorer agreement with experiment or with the results of higher-level theoretical procedures such as W1 or W2.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] The thermodynamics and kinetics of the b-fragmentation of some alkoxyl radical carrying nitrogen atoms in the b-position have been investigated at a high level of theory. [13,14] However, their orbital interactions both in the starting materials and at transition state (TS) have not been investigated although it is wellknown that stereoelectronic effects may play a major in the reactivity of organic radicals. It is known that the fragmentation requires the TS geometry to exhibit good overlapping between the SOMO and the bonding s CÀY or the antibonding s* CÀY orbitals of the cleaved CÀY bond (Figure 1 a).…”
mentioning
confidence: 99%
“…The good agreement of these two levels of theory was also suggested in a previous study for the analog ␤-scission of the peptide backbone by an alkoxyl radical. 44 As previously found for radical systems, 45 MP2 and B3LYP, respectively, overestimate (by 1-11 kcal mol -1 ) and underestimate (by 4-10 kcal mol -1 ) the barriers against the ␤-radicalinduced N-C ␣ and C ␣ -C bond cleavages. It is interesting to note that the accuracy of the pure DFT functionals, such as HCTH and PBE, is comparable with that of the B3LYP hybrid DFT functional.…”
Section: Computational Detailsmentioning
confidence: 53%